Efecto de la fertilización orgánica, edáfica y foliar sobre el desarrollo y rendimiento del cultivo de pepino (Cucumis sativus), sembrados en contenedores en la zona de Babahoyo - Bravo Robledo, Erick Heiner (2018)
VII. SUMMARY The present experimental work was carried out in the experimental farm "San Pablo", of the Faculty of Agricultural Sciences of the Babahoyo Technical University, located at Km 7.5 of the Babahoyo-Montalvo road in the province of Los Ríos. The zone presents a humid tropical climate according to the classification of Holdribge, with annual temperature of 26.3 0C, precipitation of 2791.4 mm / year, relative humidity of 76% and 804.7 hours of annual average heliophany. The geographic coordinates are west longitude 277438.26 UTM, south latitude 110597.97 UTM and altitude of 8 masl. The Jaguar cucumber hybrid was used as seed material. The proposed objectives were to determine the effects of edaphic and mineral fertilization in the Babahoyo area; identify the most suitable product and fertilizer dose in the development and yield of cucumber and economically analyze the treatments under study. The treatments that were used were Humifos-K plus Super Biol Mineralized (doses of 1.0 L + 1.0 L and 1.5 L + 1.0 L); Alga / Tec plus Super Biol Mineralized (1.0 L + 1.0 L and 1.5 L + 1.0 L); Humifos-K (1.0 L); Alga / Tec (1.0 L) and the chemical control with 100 kg / ha of N + 40 kg / ha of P + 70 kg / ha of K. The experimental design of Complete Blocks at Random was used, with seven treatments and three repetitions. To establish the comparison and statistical difference between the averages of the treatments, the Duncan test at 5% significance was used. The obtained results determined that the applications of organic fertilizers edaphic and foliar influenced so that there is more time for the variables days to flowering and harvest; the application of Humifos-K in doses of 1.0 L / ha plus Super Biol Mineralized 1.0 L / ha obtained greater length of plants; the largest diameter of the fruit was presented by the treatment that was used by the chemical control with 100 kg / ha of N + 40 kg / ha of P + 70 kg / ha of K, unlike the length of the fruit stood out with the use of Humifos -K in doses of 1.5 L / ha plus Super Biol Mineralized 1.0 L / ha; the use of Humifos-K in doses of 1.0 L / ha plus Super Biol Mineralized 1.0 L / ha reported higher fruit weight; The chemical control with 100 kg / ha of N + 40 kg / ha of P + 70 kg / ha of K obtained greater number of fruits per plant and yield and in the economic analysis, all the treatments recorded negative net benefit, due to the low obtained yield and high cost of production in the trial.